2007
DOI: 10.1097/ta.0b013e31812389d6
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Drops Within Minutes of Injuries and Predicts Need for an Intervention to Stop Hemorrhage

Abstract: Hemorrhage in trauma patients is associated with an early decrease in Hgb level. Hgb < or =10 gm/dL in the first 30 minutes of patient arrival will correctly identify presence or absence of significant bleeding in almost 9 of 10 trauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 10 publications
4
32
1
Order By: Relevance
“…Table 1 shows that initial Hct is significantly correlated with acidosis, hypotension, and mortality. This is consistent with data from Bruns et al, 16 who demonstrated significant correlation in trauma patients between the initial hemoglobin and tachycardia, systolic hypotension, low pH, and a lower base deficit. The acidosis is likely the result of systemic hypoperfusion alone, because humans tolerate significant isovolemic hemodilution without changes in systemic lactate or decreases in base deficit.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Table 1 shows that initial Hct is significantly correlated with acidosis, hypotension, and mortality. This is consistent with data from Bruns et al, 16 who demonstrated significant correlation in trauma patients between the initial hemoglobin and tachycardia, systolic hypotension, low pH, and a lower base deficit. The acidosis is likely the result of systemic hypoperfusion alone, because humans tolerate significant isovolemic hemodilution without changes in systemic lactate or decreases in base deficit.…”
Section: Discussionsupporting
confidence: 91%
“…The acidosis is likely the result of systemic hypoperfusion alone, because humans tolerate significant isovolemic hemodilution without changes in systemic lactate or decreases in base deficit. 19 Table 2 shows that patients with low initial Hct values required significantly more fluids during the initial resuscitation period, which is also consistent with data from Bruns et al 16 To our knowledge, there are no other studies demonstrating an increase in vasopressor requirements in patients with a low Hct value on admission.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the management of the patient, the presenting low haemoglobin is in keeping with recently reported literature, 3 as predicting the need for operative intervention and the initially unstable vital signs led to the implementation of a ''damage-control'' technique 2 during the laparotomy, which necessitated hysterectomy.…”
Section: Discussionmentioning
confidence: 67%
“…Frequently, Hb may be fictitiously high, not yet equilibrating to actual blood loss. In a recent study, Bruns et al obtained three Hb measurements within the first 30 min of patient arrival to the ED and identified that an early decrease in Hb level (Յ 10 g/dL) was associated with the need for emergent interventional procedures (surgical or angiographic) to stop bleeding in 87% of patients (23). They concluded that an initial Hb Յ 10 g/dL can be used as a trigger to prompt an aggressive search for sources of bleeding.…”
Section: Trauma Resuscitationmentioning
confidence: 93%